Quality of Life in Parents of Children Born with Esophageal Atresia - Witt, Stefanie; Dellenmark-Blom, Michaela; Dingemann, Jens; Dingemann, Carmen; Ure, Benno M.; Gomez, Barbara; Bullinger, Monika; Quitmann, Julia (European Journal of Pediatric Surgery, 2019)
Introduction For parents of chronically ill children, the experiences of caregiving are challenged by increased demands and restrictions imposed by their child's disease. Therefore, this study aims to investigate the quality of life (QoL) in parents of children born with esophageal atresia (EA) and to explore associated factors.Materials and Methods Parents of children (2–17 years) with EA recruited from two German pediatric hospitals participated in this cross-sectional study about QoL in EA. Data on QoL, sociodemographic, and clinical characteristics were collected from parents and children. Parental QoL was assessed using the Short-Form 8 questionnaire, containing eight dimensions aggregated to a mental and physical health summary score which was compared with German representative population norms.Results Forty-nine families (47 mothers and 40 fathers) participated in the study. Compared with German population norms, both mothers and fathers showed significantly lower mental component score (MCS) but no differences in physical component score (PCS). Within the study sample, parents of younger children (2–7 years), severe EA, or high school/kindergarten absence had lower MCSs compared with those with older, less severe, and less absent children. Parental female gender was associated with lower MCS as well as lower family income.Conclusion Parents of children with EA reported lower mental health compared with the general population, especially mothers, and parents of young children, with severe EA, and a frequent school/kindergarten absence. This shows that parents may experience substantial emotional burden and highlights the need for psychosocial support for EA parents, especially in the first years.
Keywords: esophageal atresia; quality of life; parents; children